Antibiotic susceptibility testing and molecular characterization based on whole-genome sequencing of Streptococcus pneumoniae isolates from pediatric infections at the National Regional Medical Center of Southwest China during the COVID-19 pandemic - Yan, Ziyi; Miao, Chenglin; Liu, Li; Fu, Yunhan; Liu, Xingxin; Li, Hong; Kuang, Linghan; Cui, Yali; Jiang, Yongmei (Frontiers in Public Health, 2024)
BackgroundStreptococcus pneumoniae is a transmitted respiratory pathogen that causes high morbidity and mortality in children, especially those under 5 years of age. During the implementation of population control measures for COVID-19 in mainland China, the Streptococcus pneumoniae detection rate in pediatric patients decreased. However, with the second wave of the COVID-19 pandemic (2022), the incidence of pneumococcal disease (PD) and even invasive pneumococcal disease (IPD) began to rise again.MethodsThis study was conducted from August 2022 to September 2023 at a national regional medical center based mainly in West China Second University Hospital, Sichuan University. The demographic and clinical characteristics of S. pneumoniae-infected pediatric patients were analyzed. All S. pneumoniae isolates were subjected to standardized clinical sample inoculation, culture, subculture, and identification procedures. Next-generation sequencing and analysis were used to determine serotypes and sequence types (STs) and evaluate antibiotic resistance- and virulence-related genes. Antimicrobial susceptibility was determined in AST dishes via the broth microdilution method.ResultsThe prevalent serotypes in the IPD patients were 14, 6A, and 23F, and the prevalent serotypes in the NIPD patients were 19F and 6A. A significant difference in the proportion of patients with serotype 14 was noted between the two groups. A total of 23 STs were identified and classified into 13 different GPSC lineages, including 4 novel STs (ST18449, ST18451, ST18464 and ST18466) and 1 novel allele (ddl1209). According to the interpretation breakpoints for non-meningitis infections, the resistance/nonsusceptibility rates of invasive isolates were as follows: penicillin (0.0%/8.3%), amoxicillin (0.0%/0.0%), cefotaxime (8.3%/16.6%), ceftriaxone (8.3%/8.3%), and cefepime (0.0%/8.3%). The resistance/nonsusceptibility rates of invasive isolates according to the meningitis breakpoints were as follows: penicillin (100.0%), cefotaxime (16.7%/33.4%), ceftriaxone (8.3%/50.0%), and cefepime (8.3%/66.7%). All the isolates were susceptible to rifampicin, levofloxacin, moxifloxacin, linezolid and vancomycin. In addition, the characteristics of the antibiotic resistance-related genes and virulence genes of serotype 19F were significantly different from those of the other serotypes.ConclusionThese data provide valuable information for understanding pediatric pneumococcal disease during the second outbreak of COVID-19 in Southwest China and will contribute to the prevention and treatment of S. pneumoniae infection.